Characteristics of men who have sex with men (MSM) involved in transactional sex in Paraguay - Aguilar, Gloria; Rios-González, Carlos Miguel (Medicina Clínica y Social, 2024)
Introduction: Transactional sex, defined as exchanging sex for money, drugs, or other goods, increases the risk of infection due to factors such as multiple sexual partners, inconsistent condom use, higher frequency of STIs, and socioeconomic vulnerabilities. Objective: to describe the characteristics of men who have sex with men (MSM) involved in transactional sex in Paraguay during 2020. Methodology: Cross-sectional study was carried out in Asunción, Central, Alto Paraná, and Caaguazú during the year 2020. The study variables were demographics, sexual practices and risk behaviors, substance consumption, knowledge about HIV and  frequency of HIV, Syphilis and Hepatitis B. Results: 333 MSM involved in transactional sex participated in the study, 58.86% (196) were between 20 and 29 years old. In the last six months, 52.85% (n=176) received money, drugs or other benefits in exchange for sexual relations. The  frequency of Syphilis was 13.21% (n=44), the  frequency of HIV was 13.21% (n=44) and the  frequency of Hepatitis b was 1.20% (n=4) of the sample. Conclusion: This study highlights the high vulnerability of MSM involved in transactional sex in Paraguay and the urgent need for specific, evidence-based interventions for this population.
Keywords: Sexual and Gender Minorities; Sex Work; Paraguay